Nilai-Nilai Ekonomi Islam Dalam Religiusitas Masyarakat Melayu - Saiful Bahri (IQTISHADUNA: Jurnal Ilmiah Ekonomi Kita, 2013)
This study will describe implemented Islamic economics in Malay life. As such a tradition includes by Islam religion, this community will enough for applying a part or comprehensive obedience such as zakah and so on.